Isolated coronary artery ectasia presenting as inferior-posterior STEMI-a case-based state-of-the-art review of the current literature - Giucă Adrian; Rocsoreanu Alexandru; Şerban Marilena; Roşca Monica; Iancu Maria; Carp Andrei; Deleanu Dan; Postu Marin (Sciendo, 2023)
This review is based on the case of a 71-year-old female patient, with cardiovascular risk factors, who was referred for emergency cardiological evaluation after experiencing severe anterior chest pain that had lasted for more than 5 hours at the time of admission.